First results of the EuroHeart program - András Jánosi; Zoltán Járai (Cardiologia Hungarica)
The Board of the European Society of Cardiology initiated the European Unified Registries On Heart Care Evaluation and Randomized Trials (EuroHeart) program in 2019. It was proposed to establish international cooperation involving national registers using a uniform nomenclature and data structure. The Board of the Hungarian Society of Cardiology joined the program in 2021, which was made possible by the Hungarian Myocardial Infarction Registry (HUMIR), which has been operating continuously since 2014. In the first analysis of the EuroHeart data, 40,021 patients registered for acute myocardial infarction (18,686 STEMI and 21,335 NSTEMI) treated in 2022 in 7 countries (Estonia, Iceland, Hungary, Portugal, Romania, Sweden, Singapore) were included. The data was published in 2023. Nationwide myocardial infarction registers operated in Sweden and Hungary, while regional or centre-specific data were analysed in the other countries. 39.3% of the cases analysed came from Sweden, 30.1% from Hungary, and 20.1% from Portugal. The average age is 68 years, and almost a third of the patients (31.6%) are women. Common comorbidities were hypertension and diabetes (67.9% and 28%, respectively). One in five patients (20.2%) had a history of heart attack, 6.2% had a stroke. Abnormal kidney function was confirmed in 7.5% of patients. According to data from registries covering the entire population, the frequency of PCI treatment in STEMI was 86.2% in Hungary and 91.8% in Sweden. Primary PCI treatment for STEMI patients at the optimal time (<12 h) was administered to 73% of patients, with rates varying across participating countries. In Sweden, the vessel was opened in 90.9% of the patients within 12 hours of the onset of the complaint, in Hungary this was only achieved in 46.4% of the treatments. At the time of discharge from the hospital, among the drugs important in secondary prevention, statin use was the most common (92.1%). The EuroHeart population leaving the hospital, aspirin, P2Y12 inhibitors and statins were administered with appropriate frequency (91.3%, 94.8%, 94.1%). Coronary angiography was performed in 84.4% of NSTEMI patients, and 54.1% of the treatments were performed within 24 hours from the onset of the complaint. Among the drugs used at discharge, 90.7% of NSTEMI patients received statin. The frequency of use of aspirin and P2Y12 inhibitor drugs (84.9% and 80.4%, respectively) was lower than observed in STEMI patients. There were significant differences between the countries regarding the active substances used for TAGG treatment.